Auxiliary alloy nano powder, modified magnetic powder, sintered neodymium-iron-boron magnet and preparation method
By preparing modified magnetic powders of auxiliary alloy nano powder and main alloy micro powder, the temperature stability and coercive force enhancement of traditional sintered NdFeB magnets in high temperature and high performance fields is solved, and higher magnetic performance and resistance are achieved High temperature performance.
Patent Information
- Application Number
- CN202411409955.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
传统烧结钕铁硼磁体在高温和高性能要求领域的应用受到温度稳定性和矫顽力提升的限制,现有辅合金工艺存在辅合金添加量大、矫顽力偏低、方形度偏低以及 耐高温性能未涉及的问题。
Using the preparation method of auxiliary alloy nano powder, auxiliary alloy sheets are obtained by smelting or mechanical alloying, and mixed with organic and inorganic modifiers for crushing to obtain auxiliary alloy nano powder with particle size of 20-990 nm, used to be used with main alloys. The micron powder is shear-mixed to form a modified magnetic powder, and then vacuum heat treatment is performed to prepare the sintered NdFeB magnet.
The coercive force and squareness of the sintered NdFeB magnet are improved, the residual magnetic temperature coefficient and coercive force temperature coefficient are reduced, and the magnetic performance, stability and high temperature resistance are improved.
Smart Images

Figure CN119282124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to auxiliary alloy nano powder, modified magnetic powder, sintered NdFeB magnet and preparation method thereof. Background Art
[0002] With the rapid development of low-carbon economy such as new energy vehicles and wind power generation, higher requirements are placed on the magnetic properties of sintered NdFeB magnets. However, traditional sintered NdFeB magnets have problems such as poor temperature stability and difficulty in further improving coercivity, which limits their application in fields requiring high temperature and high performance.
[0003] The auxiliary alloy process in the preparation of sintered NdFeB magnets is an important preparation process.
[0004] CN103103442A discloses a method for preparing NdFeB by main-auxiliary alloy method, comprising: the raw materials for preparing NdFeB are composed of main alloy and auxiliary alloy, wherein the main alloy component is Re x Fe (100-x-z) B z , Re is a rare earth element, which contains at least one of Nd or Pr; the auxiliary alloy is Re a Fe 100-a-y M y B b , Re is one or more of La, Ce, Y, Dy, Pr and Gd; M is one or more of the added elements Al, Co, Cu, Nb and Ga; the main and auxiliary alloys are mixed in a ratio of u:100-u, where u is a weight percentage, 70≤u<100; the main alloy and auxiliary alloy of corresponding components are prepared according to the component requirements, and then the NdFeB magnet is prepared according to the steps of smelting, crushing, molding, sintering, and tempering after sintering. In this method, the smelted main and auxiliary alloy ingots or sheets are mixed in proportion and crushed into powders with a particle size of 2.4 to 6μm. The amount of auxiliary alloy is relatively large, which is 10 to 30wt%, and heavy rare earth elements still need to be added to the auxiliary alloy of this method. The coercivity of the obtained magnet is still small, the remanence is seriously reduced, and the squareness, remanence temperature coefficient and coercivity temperature coefficient are not involved.
[0005] CN115083707A discloses a method for preparing a main-auxiliary alloy system NdFeB magnet material. The raw material composition of the NdFeB magnet material includes a main alloy raw material and an auxiliary alloy raw material. The mass percentage of the auxiliary alloy raw material in the main-auxiliary alloy raw material composition is 1.0-15.0mas%. The auxiliary alloy raw material includes the following components: light rare earth element LR, 0-30.0mas%; LR is Nd and / or Pr; heavy rare earth element HR, 1-80mas%; HR is Dy and / or Tb; M, 5.0-20.0mas%; M is selected from one or more of Co, Cu, Al and Ga; X, 3.0-12.0mas%; X is selected from one or more of Ti, Zr, Hf, Nb, W and Ta; B, 0-0.6mas%; the remainder is Fe. In the method, the main alloy sheet and the auxiliary alloy sheet are hydrogen-crushed respectively to obtain coarsely crushed powder. Then the coarsely crushed powder is finely crushed together to obtain a finely crushed powder with an average particle size of 1 to 20 μm. The jet mill crushing process of this method does not separately coat the auxiliary alloy for anti-oxidation treatment. The large particle size makes it difficult to disperse the mixed materials. The amount of auxiliary alloy added is large, and the remanence of the magnet decreases seriously. In addition, the auxiliary alloy raw material of this method needs to be added with heavy rare earth elements to obtain a higher coercive force, and it does not involve squareness, remanence temperature coefficient and coercive force temperature coefficient.
[0006] CN115747611A discloses a method for preparing an auxiliary alloy flake and a high remanence and high coercivity NdFeB permanent magnet. The auxiliary alloy raw material comprises Pr40-45%, Co1-2%, Ga0.5-1%, B0.6-0.8%, V0.1-0.2%, Ti0.3-0.7%, and the balance Fe, by mass fraction. In the method, the main alloy flake and the auxiliary alloy flake are hydrogen crushed together to obtain a coarse powder; the auxiliary alloy flake is 10-15wt% of the main alloy flake; the coarse powder is mixed with a lipid lubricant and subjected to jet milling to obtain a fine powder of 2.5-3μm. The auxiliary alloy flake used in the method is large in amount, and the auxiliary alloy particle size after jet milling is the same as that of the main alloy. The large particle size auxiliary alloy cannot evenly cover the main phase alloy particles, the magnetic powder has insufficient fluidity, and the pressure molding orientation is low. The large proportion of addition leads to low remanence and squareness of the obtained magnet, and the high temperature resistance of the magnet is not involved.
[0007] CN116013675A discloses a method for preparing a high-performance heavy rare earth-free neodymium iron boron magnet, which uses a main alloy and an auxiliary alloy sheet, wherein the auxiliary alloy sheet is prepared in a mass ratio of R2 a N 100-b-a T b, wherein N contains Fe and one or more of Al, Co, Cu, and Ga, T contains B and one or more of Ti, Zr, Nb, Hf, and V, and R2 contains at least one of Nd and Pr, and according to the weight ratio, 26wt.%≤a≤50wt.%, 0.1wt.%≤b≤8wt.%. In this method, the main alloy casting flakes and the auxiliary alloy casting flakes are mixed in proportion and hydrogen crushed to obtain hydrogen crushed powder; after adding an antioxidant to the above hydrogen crushed powder, the powder is jet milled to obtain 2-4μm fine powder. The auxiliary alloy in this method is a high-Fe alloy foil. The main and auxiliary alloys have the same particle size after jet milling together. It is impossible to achieve uniform coating of the auxiliary alloy on the surface of the main alloy particles by mixing. The squareness of the obtained magnet is still low, and the high temperature resistance of the magnet is not involved.
[0008] CN116884758A discloses a method for preparing a high-performance sintered NdFeB matrix magnetic sheet, wherein the main phase alloy and the auxiliary phase alloy are prepared into a diffused matrix magnetic sheet blank by a dual alloy process, and the dual alloy sintered NdFeB blank is processed into a matrix magnetic sheet along a non-oriented direction by combining a non-oriented direction diffusion process, wherein the main phase alloy grains in the matrix magnetic sheet have a heavy rare earth-enriched shell structure. The method obtains a main phase magnetic powder with a particle size of 3.0 μm and an auxiliary phase powder with a particle size of 2.5 μm, respectively, and then the main phase magnetic powder and the auxiliary phase powder are mixed, pressed, and vacuum heat treated to obtain a magnet. The method does not perform component design and anti-oxidation treatment on the auxiliary alloy, and the existing modifier cannot obtain high-quality auxiliary alloy materials with nano-particle size, and the squareness of the obtained sintered NdFeB magnet is low.
[0009] CN116959833A discloses an alloy raw material for a NdFeB magnet material, a NdFeB magnet material and a preparation method thereof. The alloy raw material comprises a main alloy raw material and an auxiliary alloy raw material. The main alloy raw material comprises a first light rare earth element RL1, B, Co, Cu, Al, Zr, Fe and optionally Ga, and the first light rare earth element RL1 is selected from one or more of Y, La, Ce, Pr and Nd; the auxiliary alloy raw material comprises a second light rare earth element RL2, B, Fe and M, and the second light rare earth element RL2 is selected from one or more of Y, La, Ce, Pr and Nd, and M comprises Al, Cu and Ga; based on the total weight of the auxiliary alloy raw material, the content of B in the auxiliary alloy raw material is 0.7-0.8% by weight, the content of the second light rare earth element RL2 in the auxiliary alloy raw material is 35-45% by weight, the content of M is 0.1-5.5% by weight, and the balance is Fe. In this method, a main alloy raw material with an average particle size of 4 to 4.5 μm and an auxiliary alloy raw material with an average particle size of 3.5 to 3.9 μm are obtained respectively. Then, the main alloy raw material and the auxiliary alloy raw material are mixed, pressed, and vacuum heat treated to obtain a magnet. In this method, the auxiliary alloy component lacks high melting point elements, and the particle size is close to that of the main phase alloy, and cannot be evenly coated on the surface of the magnetic powder. The coercive force and squareness of the obtained sintered NdFeB magnet are still low.
[0010] CN103123838A discloses a rare earth permanent magnet produced by using high-abundance rare earth MM and a preparation method thereof, the preparation method comprising: 1) the main alloy is melted, rapidly solidified, cast, hydrogen broken, and air flow milled to obtain the main alloy powder; 2) the auxiliary alloy is melted, roughly broken, and then mechanically ball milled with gasoline or petroleum ether as a protective medium to obtain the auxiliary alloy powder; 3) nanoparticles and auxiliary alloy powder are mixed, and the grain boundary phase is nano-modified to obtain the nano-modified auxiliary alloy powder; 4) the main alloy powder and the nano-modified auxiliary alloy powder are mixed, pressed, isostatically pressed, and vacuum heat treated to obtain the magnet. This method uses nanoparticles to modify the auxiliary alloy, but does not directly obtain the auxiliary alloy powder with a nano-particle size.
[0011] In summary, in the above methods, there are situations where the amount of auxiliary alloy added is large, the coercivity is low, the squareness is low and / or the cost is high. Moreover, the above methods basically do not involve the temperature coefficient of remanence and the temperature coefficient of coercivity, that is, they do not involve high temperature resistance. In addition, the addition of auxiliary alloys with larger particle sizes in the above methods is likely to introduce a large amount of impurity elements such as oxygen, nitrogen, and carbon, thereby reducing the performance of the magnet. Summary of the invention
[0012] In view of this, one object of the present invention is to provide a method for preparing auxiliary alloy nanopowder for modifying magnetic powder. The obtained auxiliary alloy nanopowder is beneficial to improving the coercivity and squareness of the obtained sintered NdFeB magnet, and reducing the absolute value of its residual magnetism temperature coefficient and the absolute value of the coercivity temperature coefficient. Another object of the present invention is to provide an auxiliary alloy nanopowder prepared according to the preparation method as described above. Another object of the present invention is to provide a modified magnetic powder, which is beneficial to improving the squareness of the magnet, reducing the absolute value of the residual magnetism temperature coefficient and the absolute value of the coercivity temperature coefficient of the magnet on the basis of improving the coercivity of the obtained sintered NdFeB magnet, thereby improving the magnetic properties, stability and high temperature resistance of the magnet.
[0013] Another object of the present invention is to provide a method for preparing the modified magnetic powder. Another object of the present invention is to provide a method for preparing a sintered NdFeB magnet. Another object of the present invention is to provide a sintered NdFeB magnet prepared according to the above-mentioned preparation method.
[0014] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0015] In one aspect, the present invention provides a method for preparing auxiliary alloy nanopowder for modified magnetic powder, wherein the chemical composition of the auxiliary alloy nanopowder is Re 100-m-n (Cu, X) m Q n , Re is a light rare earth element, X is selected from at least one of Al, Ga, Co, Mg, Sn, Te and Sb, Q is selected from at least one of Ti, Zr, Hf, V, Nb, Ta, W and Mo; m and n are atomic numbers, 24≤m≤72.4, 12.5≤n≤76, and 100-mn is greater than or equal to 0;
[0016] The auxiliary alloy nano powder does not contain Fe and B;
[0017] The preparation method comprises the following steps:
[0018] (1) melting or mechanically alloying the raw material of the auxiliary alloy nanopowder to obtain auxiliary alloy flakes;
[0019] (2) mixing the auxiliary alloy flakes, the modified substance and the organic solvent, and preliminarily crushing them to obtain auxiliary alloy coarse powder; and further finely crushing the auxiliary alloy coarse powder to obtain auxiliary alloy nano powder;
[0020] Wherein, the modified substance is a combination of an organic modifier and an inorganic modifier;
[0021] The organic modifier is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters, amide compounds and organic boron compounds; the amount of the organic modifier added is 2 to 20 wt% of the mass of the auxiliary alloy sheet;
[0022] The inorganic modifier is a layered substance, which is selected from at least one of molybdenum disulfide, tungsten disulfide and vanadium selenide; the addition amount of the inorganic modifier is 0.5-5wt% of the mass of the auxiliary alloy sheet.
[0023] According to the method for preparing auxiliary alloy nanopowder of the present invention, preferably:
[0024] The higher alcohol is selected from at least one of tetradecanol, hexadecanol, stearyl alcohol and eicosanol; the higher carboxylic acid is selected from at least one of erucic acid, lauric acid, palmitic acid, myristic acid and stearic acid; the higher fatty acid ester is selected from at least one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride; the amide compound is selected from at least one of oleamide, stearic acid amide and erucic acid amide; the organic boron compound is selected from at least one of triisopropyl borate, tributyl borate and triethyl borate;
[0025] The organic solvent is selected from at least one of petroleum ether, alcohols and esters;
[0026] The auxiliary alloy nano powder does not contain heavy rare earth elements.
[0027] According to the preparation method of auxiliary alloy nanopowder of the present invention, preferably, the alcohol is selected from one or more of isopropyl alcohol, p-methoxybenzyl alcohol, ethanol and α-pinene alcohol; the ester is selected from one or more of diethylene glycol butyl ether acetate, ethylene glycol diacetate, ethylene glycol ethyl ether acetate, tributyl citrate and ethyl acetate.
[0028] On the other hand, the present invention also provides an auxiliary alloy nano powder for modifying magnetic powder, which is prepared according to the preparation method as described above and has a particle size of 20 to 990 nm.
[0029] In another aspect, the present invention further provides a modified magnetic powder, which is formed by a main alloy micron powder and an auxiliary alloy nano powder prepared by the preparation method as described above; wherein the main alloy micron powder is R2Fe 14 The B-type compound is the main phase, R is selected from at least one rare earth element and must contain Nd;
[0030] The amount of the auxiliary alloy nano powder added is 0.2-1.2 wt % of the total mass of the main alloy micron powder and the auxiliary alloy nano powder.
[0031] According to the modified magnetic powder of the present invention, preferably, the particle size of the main alloy micron powder is 1.2-5.8 μm.
[0032] In another aspect, the present invention further provides a method for preparing the modified magnetic powder as described above, comprising the following steps:
[0033] 1) preparing the auxiliary alloy nano powder according to the preparation method as described above;
[0034] 2) Shear-mixing the auxiliary alloy nanopowder obtained in step 1) with the main alloy micron powder to obtain modified magnetic powder; or, mixing the auxiliary alloy nanopowder with the main alloy flakes and crushing them with a jet mill to obtain modified magnetic powder; wherein the main alloy flakes are used to form the main alloy micron powder.
[0035] According to the method for preparing the modified magnetic powder of the present invention, preferably, the main alloy micron powder is prepared by the following steps:
[0036] The raw material of the main alloy micron powder is subjected to a smelting process to obtain a main alloy flake; and then the main alloy flake is subjected to a hydrogen crushing process and a jet milling process in sequence to obtain the main alloy micron powder.
[0037] In another aspect, the present invention further provides a method for preparing a sintered NdFeB magnet, comprising the following steps:
[0038] a) providing the modified magnetic powder as described above or preparing the modified magnetic powder according to the preparation method of the modified magnetic powder as described above;
[0039] b) pressing the obtained modified magnetic powder to obtain a green body;
[0040] c) subjecting the green body to vacuum heat treatment to obtain a sintered NdFeB magnet.
[0041] According to the preparation method of the sintered NdFeB magnet of the present invention, preferably, in step c), the vacuum heat treatment includes pre-sintering the green body at 235-495°C for 0.5-3h, sintering at 1030-1105°C for 3-7h, then aging treatment at 870-950°C for 0.5-5h, and then aging treatment at 400-650°C for 1-5h to obtain a sintered NdFeB magnet.
[0042] In another aspect, the present invention further provides a sintered NdFeB magnet, which is prepared according to the preparation method described above.
[0043] The auxiliary alloy nano powder obtained by the present invention is conducive to modifying the magnetic powder, and further, on the basis of improving the remanence and coercivity of the obtained sintered NdFeB magnet, it is conducive to improving the squareness of the obtained magnet, reducing the absolute value of the remanence temperature coefficient and the absolute value of the coercivity temperature coefficient of the magnet, thereby improving the magnetic properties, stability and high temperature resistance of the magnet. According to the preferred technical solution of the present invention, the present invention obtains the modified magnetic powder by mixing the formed specific auxiliary alloy nano powder with the main alloy micro powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The SEM image of the auxiliary alloy nanopowder obtained in Example 1. In the figure, Pa1 to Pa6 are the lengths of the long sides of the corresponding particles in the auxiliary alloy nanopowder, PaR1 represents the starting point and end point of the particle measurement, and PaR2 to PaR6 have the same meaning as PaR1. Pb1 to Pb6 are the angles between the corresponding lines of the measurement starting point and end point and the horizontal direction. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0046] The "remanent magnetism" mentioned in the present invention refers to the value of the magnetic flux density corresponding to the point where the magnetic field intensity is zero on the saturation hysteresis loop, and the unit is Tesla (T) or Gauss (Gs). 1Gs = 0.0001T.
[0047] The "coercive force" mentioned in the present invention, also known as intrinsic coercive force, refers to the magnetic field intensity when the magnetic field is monotonically reduced to zero and then increased in the opposite direction from the saturated magnetization state of the magnet, so that the magnetization intensity decreases to zero along the saturation hysteresis loop, and the unit is Oersted (Oe) or Ampere / meter (A / m). 1Oe = 79.6A / m.
[0048] Remanence temperature coefficient (α Br (T)), coercivity temperature coefficient (β Hcj The definitions of (T)) are as follows, and the units of both are % / °C.
[0049]
[0050] In the formula, B r (T) is the remanence at temperature T, B r (T0) is the remanence at T0. Hcj(T) is the coercivity at T, and Hcj(T0) is the coercivity at T0. The smaller the absolute value of the remanence temperature coefficient and the absolute value of the coercivity temperature coefficient, the smaller the change of the remanence and coercivity with temperature.
[0051] In the present invention, the "vacuum degree" refers to absolute vacuum degree; the smaller the value, the higher the vacuum degree. The "inert atmosphere" refers to an environment formed by inert gases such as helium, neon, argon, krypton and xenon.
[0052] <Auxiliary alloy nanopowder and preparation method>
[0053] The chemical composition of the auxiliary alloy nano powder of the present invention is Re 100-m-n (Cu, X) m Q n .
[0054] Re is a light rare earth element, and Re is selected from at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and europium (Eu). Preferably, Re is selected from one of cerium (Ce), praseodymium (Pr), and neodymium (Nd).
[0055] X is selected from at least one of Al, Ga, Co, Mg, Sn, Te and Sb, preferably, X is selected from at least one of Al, Ga, Co, Mg, Sn and Sb, more preferably Al and / or Ga. Q is selected from at least one of Ti, Zr, Hf, V, Nb, Ta, W and Mo, preferably at least one of Ti, Zr and Nb.
[0056] m is the number of atoms, 24≤m≤72.4, preferably, 28≤m≤68, more preferably, 30≤m≤60.
[0057] n is the number of atoms, 12.5≤n≤76, preferably, 20≤n≤76, more preferably, 27≤n≤76, further preferably, 30≤n≤70, and further preferably, 30≤n≤58. 100-mn is greater than or equal to 0, preferably, 100-mn is greater than or equal to 0 and less than or equal to 40.
[0058] The auxiliary alloy nano powder does not contain heavy rare earth elements, Fe and B.
[0059] The preparation method of auxiliary alloy nano powder of the present invention comprises the following steps:
[0060] (1) melting or mechanically alloying the raw material of the auxiliary alloy nanopowder to obtain auxiliary alloy flakes;
[0061] (2) The auxiliary alloy flakes, the modified substance and the organic solvent are mixed and preliminarily crushed to obtain auxiliary alloy coarse powder; and the auxiliary alloy coarse powder is further finely crushed to obtain auxiliary alloy nano powder.
[0062] In step (1), the raw material of the auxiliary alloy nanopowder can be subjected to a smelting process to obtain auxiliary alloy flakes. In the present invention, the smelting process is a process known in the art, and may include smelting the raw material of the auxiliary alloy nanopowder, and rapidly solidifying and spinning to obtain auxiliary alloy flakes. In order to prevent the raw material and the alloy flakes obtained therefrom from being oxidized, the smelting is carried out in a vacuum or inert atmosphere. The smelting process preferably adopts a rapid solidification casting process. Rapid solidification casting is to rapidly cool and solidify the smelted auxiliary alloy raw material and spin it into auxiliary alloy flakes. The temperature during smelting can be 1400-1500°C. The thickness of the auxiliary alloy flakes can be 0.01-2 mm, preferably 0.1-1.5 mm, and more preferably 0.15-0.5 mm.
[0063] Mechanical alloying specifically refers to a complex physical and chemical process in which mechanical energy is used to cause powder particles to undergo repeated collisions, deformations, cold welding, and crushing to achieve alloying at the atomic level, usually with the aid of a high-energy grinder or ball mill.
[0064] In step (2), the auxiliary alloy flakes, the modifying substance and the organic solvent are mixed and preliminarily crushed to obtain auxiliary alloy coarse powder; and the auxiliary alloy coarse powder is further finely crushed to obtain auxiliary alloy nano powder.
[0065] The organic solvent is selected from one or more of alcohols, esters and petroleum ether. The alcohol is selected from at least one of isopropyl alcohol, p-methoxybenzyl alcohol, ethanol and α-terpineol. The ester is selected from one or more of diethylene glycol butyl ether acetate, ethylene glycol diacetate, ethylene glycol ethyl ether acetate, tributyl citrate and ethyl acetate.
[0066] The modified substance is a composition of an organic modifier and an inorganic modifier. The amount of the organic modifier added is 2-20wt% of the weight of the auxiliary alloy flakes, preferably 3-12wt%, and more preferably 6-9wt%. The amount of the inorganic modifier added is 0.5-5wt% of the weight of the auxiliary alloy flakes, preferably 0.5-2wt%, and more preferably 0.6-3wt%. This is conducive to obtaining auxiliary alloy nanopowders with small size, good fluidity, and good antioxidant properties.
[0067] The organic modifier is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters, amide compounds and organic boron compounds. The higher alcohol is selected from at least one of tetradecanol, hexadecanol, octadecyl alcohol and eicosanol. The higher carboxylic acid is selected from at least one of erucic acid, lauric acid, palmitic acid, myristic acid and stearic acid. The higher fatty acid ester is selected from at least one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride. The amide compound is selected from at least one of oleamide, stearic acid amide and erucic acid amide. The organic boron compound is selected from at least one of triisopropyl borate, tributyl borate and triethyl borate.
[0068] The inorganic modifier is a layered substance, which is selected from at least one of molybdenum disulfide, tungsten disulfide and vanadium selenide.
[0069] In some specific embodiments, the modifying substance is a combination of stearic acid amide and molybdenum disulfide. In other specific embodiments, the modifying substance is a combination of lauric acid and molybdenum disulfide.
[0070] In the present invention, the auxiliary alloy coarse powder can be further finely crushed through a jet milling process to obtain auxiliary alloy nano powder.
[0071] The particle size of the obtained auxiliary alloy nano powder is 50 to 990 nm, preferably 80 to 900 nm, more preferably 100 to 800 nm, and further preferably 120 to 650 nm. The surface of the auxiliary alloy nano powder is covered with a modifying substance.
[0072] The present invention believes that the auxiliary alloy nano powder thus obtained, on the one hand, the high content of Q element therein can be used as a strong carbide element to react with the impurity carbon element that has not been decarbonized to form a high melting point compound, chemically solidify to eliminate the harm of the impurity element, and at the same time, the high melting point compound formed is distributed at the grain boundary, inhibiting the growth of the main phase grains of the magnet, strengthening the mechanical properties of the magnet, shaping the high-quality distribution morphology of the neodymium-rich phase, and the Q element partially dissolved in the neodymium-rich phase can improve the service performance of the obtained sintered magnet, such as high temperature stability. On the other hand, the auxiliary alloy nano powder of the present invention has a small size, good fluidity, and good oxidation resistance, and can be used as a lubricating modifier for the main alloy micron powder, solving the outstanding problems of uneven mixing, insufficient oxidation, and poor fluidity of the auxiliary alloy powder and the main alloy powder existing in the prior art.
[0073] <Modified magnetic powder and preparation method>
[0074] Modified magnetic powder
[0075] The modified magnetic powder provided by the present invention is formed by the main alloy micron powder and the auxiliary alloy nano powder prepared as above. Such modified magnetic powder is more conducive to improving the remanence, coercive force and squareness of the obtained magnet and reducing the absolute value of the remanence temperature coefficient and the absolute value of the coercive force temperature coefficient.
[0076] When the main alloy micron powder of the present invention is formed into a magnet, R2Fe 14The B-type compound is the main phase, and R is selected from at least one rare earth element and must contain Nd. R can be a light rare earth element, or R can be a light rare earth element and a heavy rare earth element. The light rare earth element is at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and europium (Eu), preferably praseodymium (Pr) and neodymium (Nd). The heavy rare earth element is at least one of gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu) and yttrium (Y), preferably terbium (Tb) or dysprosium (Dy). According to one embodiment of the present invention, R is selected from at least one element of Pr and Nd, and must contain Nd. According to a preferred embodiment of the present invention, R is Nd and Pr.
[0077] In the present invention, the main alloy micron powder may contain one or more of Ga, Cu, Al, Co, Zr and Ti in addition to the elements R, B and Fe.
[0078] The chemical composition of the auxiliary alloy nanopowder is Re 100-m-n (Cu, X) m Q n .
[0079] Among them, Re is a light rare earth element, and Re is selected from at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and europium (Eu). Preferably, Re is selected from one of cerium (Ce), praseodymium (Pr), neodymium (Nd).
[0080] X is selected from at least one of Al, Ga, Co, Mg, Sn, Te and Sb, preferably, X is selected from at least one of Al, Ga, Co, Mg, Sn and Sb, more preferably Al and / or Ga. Q is selected from at least one of Ti, Zr, Hf, V, Nb, Ta, W and Mo, preferably at least one of Ti, Zr and Nb. m is the number of atoms, 24≤m≤72.4, preferably, 28≤m≤68, more preferably, 30≤m≤60.
[0081] n is the number of atoms, 12.5≤n≤76, preferably, 20≤n≤76, more preferably, 27≤n≤76, further preferably, 30≤n≤70, and further preferably, 30≤n≤58. 100-mn is greater than or equal to 0, preferably, 100-mn is greater than or equal to 0 and less than or equal to 40.
[0082] The auxiliary alloy nano powder does not contain heavy rare earth elements, Fe and B.
[0083] The amount of the auxiliary alloy nano powder added is 0.2-1.2wt% of the sum of the mass of the main alloy micron powder and the auxiliary alloy nano powder, preferably 0.2-1.0wt%, more preferably 0.4-0.8wt%. For example, it can be 0.2wt%, 0.3wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%.
[0084] According to a specific embodiment of the present invention, the mass ratio of the main alloy micron powder to the auxiliary alloy nano powder can be selected from one of the following ratios: 98.8:0.2; 99.5:0.5; 99.4:0.6; 99.2:0.8; 99.0:1.0; or 98.8:1.2.
[0085] The particle size of the main alloy micron powder is 1.2 to 5.8 μm, preferably 2.2 to 5.2 μm, and more preferably 2.5 to 4.5 μm. The particle size and source of the auxiliary alloy nano powder are as mentioned above and will not be described here.
[0086] Preparation method of modified magnetic powder
[0087] The present invention provides a method for preparing the modified magnetic powder as described above, comprising: a preparation step of auxiliary alloy nanopowder; a mixing step. Optionally, it also comprises a preparation step of main alloy micron powder. The method is described in detail below.
[0088] The steps for preparing the auxiliary alloy nanopowder are as described above and will not be repeated here.
[0089] In the present invention, the main alloy micron powder can be obtained by subjecting the raw materials of the main alloy micron powder to a smelting process, a hydrogen crushing process and a jet milling process in sequence.
[0090] The smelting process, hydrogen crushing process and airflow milling process are all known processes in the art. The smelting process includes smelting the alloy raw material of the main alloy micron powder and rapidly solidifying it to obtain the main alloy sheet. In order to prevent the raw material and the alloy sheet obtained therefrom from being oxidized, the smelting is carried out in a vacuum or inert atmosphere. The smelting process preferably adopts a rapid solidification casting process. Rapid solidification casting is to rapidly cool and solidify the smelted main alloy raw material and throw it into the main alloy sheet. The temperature during smelting can be 1400-1500°C.
[0091] The hydrogen crushing process includes the following steps: firstly, the main alloy sheet absorbs hydrogen, the volume expansion of the alloy sheet crystal lattice is caused by the reaction between the main alloy sheet and hydrogen to crush the main alloy sheet, and then heating is performed for dehydrogenation to obtain the main alloy initial magnetic powder. The hydrogen pressure used in the hydrogen crushing is 0.02-0.2MPa, preferably 0.05-0.1MPa. The vacuum dehydrogenation temperature is 400-800°C, preferably 500-600°C.
[0092] The airflow milling process is to use airflow to accelerate the initial magnetic powder of the main alloy and then collide with each other to break it. The airflow can be a nitrogen flow, preferably a high-purity nitrogen flow. The pressure of the airflow can be 0.1-2.0 MPa, preferably 0.5-1.0 MPa, and more preferably 0.6-0.7 MPa.
[0093] According to one embodiment of the present invention, the auxiliary alloy nanopowder is shear-mixed with the main alloy micron powder to obtain modified magnetic powder. Such modified magnetic powder is conducive to forming a sintered NdFeB magnet with higher remanence, coercivity, squareness, and lower remanence temperature coefficient and coercivity temperature coefficient.
[0094] In the present invention, the shear mixing can adopt a known high-efficiency shear mixer. In the present invention, there is no need to add additional commercial antioxidants.
[0095] According to another embodiment of the present invention, the auxiliary alloy nanopowder is crushed by adding hydrogen to the primary alloy initial magnetic powder, and then crushed by air flow milling to obtain modified magnetic powder in which the auxiliary alloy nanopowder is uniformly dispersed in the primary alloy micron powder. When the melting point of the modified substance coated on the surface of the auxiliary alloy is greater than 80°C, the auxiliary alloy nanopowder is preferably added to the air flow milling process with the primary alloy initial magnetic powder to obtain the modified magnetic powder, otherwise, the auxiliary alloy nanopowder and the primary alloy micron powder are preferably added to the high-efficiency shear mixer air flow milling alloy powder to obtain the modified magnetic powder.
[0096] According to another embodiment of the present invention, the auxiliary alloy nano powder is mixed with the main alloy flakes and then crushed by air flow mill to obtain modified magnetic powder; wherein the main alloy flakes are used to form the main alloy micron powder.
[0097] <NdFeB magnet and preparation method>
[0098] The method for preparing a sintered NdFeB magnet of the present invention comprises the following steps:
[0099] a) providing the modified magnetic powder as described above or preparing the modified magnetic powder according to the preparation method of the modified magnetic powder as described above;
[0100] b) pressing the obtained modified magnetic powder to obtain a green body;
[0101] c) subjecting the green body to vacuum heat treatment to obtain a sintered NdFeB magnet.
[0102] A detailed description is given below.
[0103] In step a), the specific contents and preparation methods of the modified magnetic powder are as mentioned above and will not be described in detail here.
[0104] In step b), the modified magnetic powder is placed in a magnetic field and pressed, and the isostatic pressing treatment is omitted to obtain a green body. In order to prevent the modified magnetic powder from being oxidized, the pressing is carried out in a vacuum or inert atmosphere. The pressing process preferably adopts a mold pressing process. The orientation magnetic field direction and the magnetic powder pressing direction are oriented parallel to each other or perpendicular to each other, preferably perpendicular to each other. There is no particular restriction on the intensity of the orientation magnetic field, which can be determined according to actual needs. The magnetic field strength is greater than or equal to 1.5T, preferably greater than or equal to 1.75T, and more preferably greater than or equal to 2.0T.
[0105] In some embodiments, the modified magnetic powder is placed in a magnetic field for orientation and once formed to obtain a green body, and the density of the green body can be 3.0 to 6.0 g / cm 3 , preferably 3.5 to 5.0 g / cm 3 , more preferably 4.0 to 4.6 g / cm 3 ; Here, isostatic pressing is omitted and the green body is obtained directly. In actual production, isostatic pressing is more commonly used, but isostatic pressing has the disadvantages of low green body forming rate, easy deformation of green body, rupture of packaging material causing medium oil to enter green body and contaminate green body. Those skilled in the art know that isostatic pressing is a relatively cumbersome process. It is an improvement if isostatic pressing can be omitted. Usually, omitting isostatic pressing is called non-isostatic pressing. In the present invention, the modified magnetic powder obtained by a specific method is directly placed in a magnetic field for pressing, so that a dense green body can be obtained, so that the isostatic pressing can be omitted.
[0106] In step c), the green body is subjected to vacuum heat treatment to obtain a sintered NdFeB magnet. This is conducive to maintaining a high remanence and coercive force of the obtained magnet. The vacuum heat treatment process is carried out in a vacuum sintering furnace.
[0107] The vacuum degree during vacuum heat treatment is less than or equal to 1.0×10 -1 Pa is preferably less than or equal to 1.0×10 -2 Pa, more preferably less than or equal to 1.0×10 -3 Pa.
[0108] Vacuum heat treatment includes pre-sintering, primary heat treatment (i.e. sintering) and two aging treatments. The temperature of pre-sintering can be 235-495°C, and the holding time can be 0.5-3h. The holding temperature of the primary heat treatment can be 950-1100°C, preferably 1000-1100°C, and more preferably 1050-1090°C. The holding time of the primary heat treatment can be 2-10h, preferably 2.5-8h, and more preferably 3-6h. The holding temperature of the primary aging treatment can be 875-950°C, preferably 890-940°C, and more preferably 910-930°C. The holding time of the primary aging treatment can be 0.5-5h, preferably 1-3h, and more preferably 1-2h. The holding temperature of the secondary aging treatment can be 420-650°C, preferably 450-600°C, and more preferably 470-520°C. The holding time of the secondary aging treatment may be 1 to 6 hours, preferably 2 to 5 hours, and more preferably 3 to 4 hours.
[0109] The oxygen content of the sintered NdFeB magnet of the present invention is lower than 700ppm, preferably lower than 500ppm; the C content is lower than 800ppm, preferably lower than 600ppm; and the N content is lower than 550ppm, preferably lower than 400ppm, which is beneficial to improve the coercive force of the obtained magnet.
[0110] <Test Method>
[0111] SEM measurement: Zeiss Sigma 500 field emission scanning electron microscope was used for testing.
[0112] Determination of magnetic properties: The obtained sintered NdFeB magnets were cut into cylinders with a diameter of 10 mm and a height of 8 mm for magnetic property testing. The model of the testing instrument used was NIM-10000HC. The remanence Br and coercivity Hcj were obtained. The remanence temperature coefficient was obtained by testing the remanence at T0 of 20°C and T of 180°C, and then calculating it by the formula. The coercivity temperature coefficient was obtained by testing the coercivity at T0 of 20°C and T of 180°C, and then calculating it by the formula.
[0113] Example 1
[0114] Preparation steps of auxiliary alloy nanopowder: prepare the raw materials of auxiliary alloy nanopowder, whose chemical composition is (Cu, Al) 42 Ti 58(42, 58 refer to the number of atoms; the atomic ratio of Cu and Al is 3:2), and does not contain any rare earth elements. The prepared raw materials of the auxiliary alloy nanopowder are subjected to a smelting process to obtain auxiliary alloy flakes with a thickness of 0.3 mm. Petroleum ether is added to the auxiliary alloy flakes, and stearic acid amide (the amount of stearic acid amide added is 5wt% of the mass of the auxiliary alloy flakes) and molybdenum disulfide (the amount added is 0.5wt% of the mass of the auxiliary alloy flakes) are added as modifying substances, and a disc mill is used for preliminary crushing to obtain auxiliary alloy coarse powder; then the auxiliary alloy coarse powder is further finely crushed by ball milling to obtain auxiliary alloy nanopowder. The SEM of the obtained auxiliary alloy nanopowder is shown Figure 1 . Figure 1 The auxiliary alloy nanopowder is composed of large and small particles, with the largest particle size of 988.2nm, but it is rare, and most of the particles are dispersed particles with a particle size between 100 and 200nm. There are no obvious sharp protrusions on the surface of the particles, showing an ellipsoidal and nearly spherical appearance. It is relatively dispersed and basically has no agglomeration.
[0115] Preparation steps of main alloy micron powder: The raw material of the main alloy micron powder is subjected to a smelting process, a hydrogen crushing process and a jet milling process to obtain the main alloy micron powder, and the particle size thereof is 3.2 to 4.8 μm. The element composition of the raw material of the main alloy micron powder is as follows: PrNd 30.25wt% (the weight ratio of Pr to Nd is 1:3), Cu 0.25wt%, Al 0.12wt%, Co0.65wt%, Ga 0.2wt%, B 0.96wt%, and Fe balance.
[0116] The steps for obtaining the modified magnetic powder are as follows: adding auxiliary alloy nano powder to main alloy micro powder, the mass ratio of auxiliary alloy nano powder to main alloy micro powder is 0.8:99.2, and then shearing and mixing in a high-efficiency shear mixer for 45 minutes to obtain modified magnetic powder.
[0117] The steps of obtaining sintered NdFeB magnets are as follows: orient the modified magnetic powder in one step and omit isostatic pressing to obtain a green body with a density of 4.25 g / cm 3 ; Place the green body into a vacuum sintering furnace and enter a vacuum degree of 10 -3 Pa, start power sintering, pre-sinter at 385℃ for 1h; then sinter at 1084℃ for 4h, and the vacuum degree during the sintering stage reaches 10 -3 ~10 -4 Pa, after sintering and heat preservation, blast cooling to room temperature is performed to obtain a sintered magnet; the sintered magnet is aged at 920°C for 1.5h, then aged at 490°C for 3h, and after the heat preservation is completed, it is quickly cooled to room temperature to obtain a sintered NdFeB magnet.
[0118] The test results of the magnet performance are shown in Table 1.
[0119] Comparative Example 1
[0120] The difference from Example 1 is that the auxiliary alloy nanopowder is not used, but the raw material of the auxiliary alloy nanopowder is mixed with the raw material of the main alloy micron powder, and the magnetic powder is prepared by the preparation method of the main alloy micron powder. Then the magnetic powder is pressed and vacuum heat treated according to the method of Example 1 to obtain a sintered NdFeB magnet. The performance test results of the magnet are shown in Table 1.
[0121] Comparative Example 2
[0122] In this comparative example, when preparing the auxiliary alloy powder, only stearic acid amide is added as the modifying material, and molybdenum disulfide is not added. The total amount of the modifying material added remains unchanged. The obtained auxiliary alloy agglomerates more seriously, and the powder particle size ranges from 0.85 to 5.8 μm. The auxiliary alloy powder particle size is concentrated between 2 and 3 μm, which is close to the particle size of the main phase alloy. The other steps and parameters are the same as those in Example 1. The performance test results of the obtained magnet are shown in Table 1.
[0123] Comparative Example 3
[0124] In this comparative example, when preparing the auxiliary alloy powder, only molybdenum disulfide is added as the modifying material, and stearic acid amide is not added. The total amount of the modifying material added remains unchanged. The particle size of the obtained auxiliary alloy powder is 3.2 to 5.6 μm. The other steps and parameters are the same as those in Example 1. The performance test results of the obtained magnet are shown in Table 1.
[0125] Example 2
[0126] Preparation steps of auxiliary alloy nanopowder: prepare the raw material of auxiliary alloy nanopowder, whose chemical composition is Pr 25 (Cu, Ga) 32 Zr 43 (The atomic ratio of Cu and Ga is 4:1). The prepared raw material of auxiliary alloy nanopowder is subjected to a smelting process to obtain auxiliary alloy flakes with a thickness of 0.8 mm. Petroleum ether is added to the auxiliary alloy flakes, and lauric acid (the amount added is 6.8wt% of the mass of the auxiliary alloy flakes) and molybdenum disulfide (the amount added is 0.5wt% of the mass of the auxiliary alloy flakes) are added as modifying substances. The auxiliary alloy coarse powder is initially crushed by a disc mill to obtain the auxiliary alloy coarse powder; the auxiliary alloy coarse powder is further finely crushed by a ball mill to obtain a particle size D 50 It is an auxiliary alloy nano powder of 154nm.
[0127] Preparation steps of main alloy micron powder: The raw material of the main alloy micron powder is subjected to a smelting process, a hydrogen crushing process and a jet milling process to obtain the main alloy micron powder, and the particle size thereof is 3.2 to 4.8 μm. The element composition of the raw material of the main alloy micron powder is as follows: PrNd 30.8wt% (the weight ratio of Pr to Nd is 1:3), Cu 0.2wt%, Al 0.1wt%, Co0.9wt%, Ga0.3wt%, B 0.97wt%, and Fe balance.
[0128] The steps for obtaining the modified magnetic powder are as follows: adding auxiliary alloy nano powder to main alloy micro powder, the mass ratio of auxiliary alloy nano powder to main alloy micro powder is 0.6:99.4, and then shearing and mixing in a high-efficiency shear mixer for 45 minutes to obtain the modified magnetic powder.
[0129] The steps of obtaining sintered NdFeB magnets are as follows: orienting the modified magnetic powder in one step and omitting isostatic pressing to obtain a green body with a density of 4.20 g / cm 3 ; Place the green body into a vacuum sintering furnace and enter a vacuum degree of 10 -3 Pa, start power sintering, pre-sinter at 400℃ for 0.8h; then sinter at 1086℃ for 3h, and the vacuum degree reaches 10 -3 ~10 -4 Pa, after sintering and heat preservation, blast cooling to room temperature is performed to obtain a sintered magnet; the sintered magnet is aged at 910°C for 1h, then aged at 490°C for 2h, and after the heat preservation is completed, it is quickly cooled to room temperature to obtain a sintered NdFeB magnet.
[0130] The performance test results of the magnet are shown in Table 1.
[0131] Comparative Example 4
[0132] The difference from Example 2 is that the auxiliary alloy nanopowder is not used, but the raw material of the auxiliary alloy nanopowder is mixed with the raw material of the main alloy micron powder, and the magnetic powder is prepared by the preparation method of the main alloy micron powder. Then the magnetic powder is pressed and vacuum heat treated according to the method of Example 2 to obtain a sintered NdFeB magnet. The performance test results of the magnet are shown in Table 1.
[0133] Comparative Example 5
[0134] In this comparative example, when preparing the auxiliary alloy powder, only lauric acid was added as the modifying substance, and molybdenum disulfide was not added. The total amount of the modifying substance added remained unchanged. The particle size D of the obtained auxiliary alloy powder 50 The other steps and parameters are the same as those in Example 2. The performance test results of the obtained magnet are shown in Table 1.
[0135] Comparative Example 6
[0136] In this comparative example, when preparing the auxiliary alloy powder, only molybdenum disulfide was added as the modifying substance, and lauric acid was not added. The total amount of the modifying substance added remained unchanged. The particle size D of the obtained auxiliary alloy powder 50 The other steps and parameters are the same as those in Example 2. The performance test results of the obtained magnet are shown in Table 1.
[0137] Table 1
[0138]
[0139] In summary, the present invention forms a specific auxiliary alloy nanopowder through a specific preparation method, and then forms a specific modified magnetic powder from the auxiliary alloy nanopowder and the main alloy micron powder, which is beneficial to improving the squareness and reducing the absolute value of the residual magnetism temperature coefficient and the absolute value of the coercive force temperature coefficient on the basis of ensuring the improvement of remanence and coercivity, so that a sintered NdFeB magnet with good magnetic properties, high temperature resistance and good stability can be obtained.
[0140] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing auxiliary alloy nanopowder for modified magnetic powder, characterized in that: The chemical composition of the auxiliary alloy nano powder is Re 100-m-n (Cu, X) m Q n , Re is a light rare earth element, X is selected from at least one of Al, Ga, Co, Mg, Sn, Te and Sb, Q is selected from at least one of Ti, Zr, Hf, V, Nb, Ta, W and Mo; m and n are atomic numbers, 24≤m≤72.4, 12.5≤n≤76, and 100-mn is greater than or equal to 0; The auxiliary alloy nano powder does not contain Fe and B; The preparation method comprises the following steps: (1) melting or mechanically alloying the raw material of the auxiliary alloy nanopowder to obtain auxiliary alloy flakes; (2) mixing the auxiliary alloy flakes, the modified substance and the organic solvent, and preliminarily crushing them to obtain auxiliary alloy coarse powder; and further finely crushing the auxiliary alloy coarse powder to obtain auxiliary alloy nano powder; Wherein, the modified substance is a combination of an organic modifier and an inorganic modifier; The organic modifier is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters, amide compounds and organic boron compounds; the amount of the organic modifier added is 2 to 20 wt% of the mass of the auxiliary alloy sheet; The inorganic modifier is a layered substance, which is selected from at least one of molybdenum disulfide, tungsten disulfide and vanadium selenide; the addition amount of the inorganic modifier is 0.5-5wt% of the mass of the auxiliary alloy sheet.
2. The preparation method according to claim 1, characterized in that: The higher alcohol is selected from at least one of tetradecanol, hexadecanol, stearyl alcohol and eicosanol; the higher carboxylic acid is selected from at least one of erucic acid, lauric acid, palmitic acid, myristic acid and stearic acid; the higher fatty acid ester is selected from at least one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride; the amide compound is selected from at least one of oleamide, stearic acid amide and erucic acid amide; the organic boron compound is selected from at least one of triisopropyl borate, tributyl borate and triethyl borate; The organic solvent is selected from at least one of petroleum ether, alcohols and esters; The auxiliary alloy nano powder does not contain heavy rare earth elements.
3. A kind of auxiliary alloy nano powder for modifying magnetic powder, characterized in that: The particle size of the particle is 20 to 990 nm.
4. A modified magnetic powder, characterized in that: The invention is formed by a main alloy micron powder and an auxiliary alloy nano powder prepared by the preparation method according to claim 1 or 2; wherein the main alloy micron powder is R2Fe 14 The B-type compound is the main phase, R is selected from at least one rare earth element and must contain Nd; The amount of the auxiliary alloy nano powder added is 0.2-1.2 wt % of the total mass of the main alloy micron powder and the auxiliary alloy nano powder.
5. The modified magnetic powder according to claim 4, characterized in that: The particle size of the main alloy micron powder is 1.2-5.8 μm.
6. A method for preparing modified magnetic powder according to any one of claims 4 to 5, characterized in that: The following steps are involved: 1) preparing the auxiliary alloy nanopowder according to the preparation method according to claim 1 or 2; 2) Shear-mixing the auxiliary alloy nanopowder obtained in step 1) with the main alloy micron powder to obtain modified magnetic powder; or, mixing the auxiliary alloy nanopowder with the main alloy flakes and crushing them with a jet mill to obtain modified magnetic powder; wherein the main alloy flakes are used to form the main alloy micron powder.
7. The method for preparing modified magnetic powder according to claim 6, characterized in that: The main alloy micron powder is prepared by the following steps: The raw material of the main alloy micron powder is subjected to a smelting process to obtain a main alloy flake; and then the main alloy flake is subjected to a hydrogen crushing process and a jet milling process in sequence to obtain the main alloy micron powder.
8. A method for preparing a sintered NdFeB magnet, characterized in that: The following steps are involved: a) providing the modified magnetic powder according to claim 4 or the modified magnetic powder preparation method according to claim 6 to obtain the modified magnetic powder; b) pressing the obtained modified magnetic powder to obtain a green body; c) subjecting the green body to vacuum heat treatment to obtain a sintered NdFeB magnet.
9. The method for preparing a sintered NdFeB magnet according to claim 8, characterized in that: In step c), the vacuum heat treatment includes pre-sintering the green body at 235-495°C for 0.5-3h, sintering at 1030-1105°C for 3-7h, aging at 870-950°C for 0.5-5h, and then aging at 400-650°C for 1-5h to obtain a sintered NdFeB magnet.
10. A sintered NdFeB magnet, characterized in that: It is prepared according to the preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Method for preparing neodymium-iron-boron material through main-auxiliary alloy method
CN103103442A
Rare earth permanent magnet produced by applying abundant rare earth MM and preparation method thereof
CN103123838A
Preparation method and application of high-performance sintered neodymium-iron-boron matrix magnetic sheet
CN116884758A
Cited By
Preparation method of auxiliary alloy powder with nanometer particle size
CN121551624A
Neodymium-iron-boron material and preparation method and application thereof
CN121768845A